Art in Ukraine between identity construction and anti-colonial resistance
1 online resource (xvii, 186 pages)
Keywords: "Art in Ukraine Between Identity Construction and Anti-Colonial Resistance This edited volume traces the development of art practices in Ukraine from the 2004 Orange Revolution, through the 2013-14 Revolution of Dignity, to the ongoing Russian war of aggression. Contributors explore how transformations of identity, the emergence of participatory democracy, relevant changes to cultural institutions, and the realization of the necessity of decolonial release have influenced the focus and themes of contemporary art practices in Ukraine. Chapters analyze such important topics as the postcolonial retrieval of the past, the deconstruction of post-Soviet visualities, representations of violence and atrocities in the ongoing Russian war against Ukraine, and the notion of art as a mechanism of civic resistance and identity-building. The book will be of interest to scholars of art history, Eastern European studies, cultural studies, decolonial studies, and postcolonial studies"--